"The Arctic sea of the blogosphere": The blogosphere, as a new type of media, and the business models for blogs - Király, András László (The Hungarian Journal of Marketing and Management, 2019)
The blogs and the blogosphere became parts of our everyday life. The aim of this paper is to introduce and define the blogosphere, and to reveal that it is a new and individual type of media. In my opinion, the blogosphere is not a substitute, but a complementary of the old media. According to this finding, I assume that blogs as new media products have business potential. After summarizing the potential business models for blogs, I introduce, the Arctic-sea model, which aim is to give a guideline to the blogs, and bloggers, to what type of business models should they use for the profitable operation.